(untitled) (CIPEEX, 2025)
The pharmaceutical industry has a great global economic and social impact, but in Brazil it still faces challenges of innovation and production. The fractionation of medicines, regulated by ANVISA (RDC No. 80/2006), emerges as an alternative to expand the population’s access, reduce waste and losses, combat self-medication and promote the rational use of medicines, especially in the case of antimicrobials. This study analyzed the registrations of drugs with "Fractional Presentation" granted by the National Health Surveillance Agency (ANVISA) between 2019 and 2021, focusing on antimicrobials from the National List of Essential Medicines, RENAME. Data collection returned a total of 138 records, of which only 41.7% presented registrations of drugs with fractional presentation linked to the components of RENAME, while 20.8% of the records were invalid or expired from commercialization with ANVISA. It was also observed that 37.5% of the drugs are registered, but do not consider the proper presentation for fractionation. Among the antimicrobial drugs surveyed, Azithromycin 500 mg tablet was the most representative drug with 50% of valid registrations, followed by Metronidazole 400 mg tablet (40%) and Clarithromycin 500 mg tablet (33%). It was observed, however, that about 89% of the industries do not offer fractionated products in their portfolios, showing that this practice is not yet consolidated in the practice of the Brazilian pharmaceutical industry. Considering that pharmaceutical presentations in large volumes contribute to waste and the risk of self-medication, fractionation represents an effective strategy to optimize resources, improve therapeutic adherence and reduce environmental impacts. In the public sector, fractional packaging enables resource savings and favors sustainable public management. In the private sector, it alleviates drug costs for families and companies. In view of the above scenario, it can be stated that the effective implementation of fractionation of medicines depends mainly on the engagement and adherence of the pharmaceutical industries in making medicines available in their fractional presentations, in addition to the need for educational campaigns aimed at educating the population on the subject and encouraging continuing education by health professionals, in order to consolidate a more accessible health system. rational and sustainable.